Pedagogías en tiempos inciertos: Valoración de identidades desde una mirada inclusiva - Aranda Parra, Virginia Gabriela; Bravo Palma, Daniela Paz; Rey Figueroa, Valeria Isabel (Universidad de Costa Rica, 2021)
Today society and education face enormous challenges. If we can overcome the health emergency that the pandemic context has imposed on us, we will be able to build a new life and society, from other parameters and epistemologies that are more supportive and of social justice. For this reason, we share a systematization of a situated pedagogical experience, which questions the homogenization and decontextualization of the curriculum and puts the student body with their interests and concerns at the center. From our pedagogical exercise we promote a new education that supports a more humanistic and inclusive proposal, from other epistemic and didactic approaches, which imply the transformation of old reproductive, assimilationist and segregating practices, to move towards a greater understanding of diversity. For this reason, we have built and used dialogical and participatory pedagogical practices, designed from critical approaches and based on orientations contained in a pedagogy per project, which allowed venturing into such complex, diverse and everyday territories from the experiences of the students. This innovation was developed in an online course via zoom offered in the training program "Minor of the Metropolitan University of Education Sciences", Santiago de Chile, on cross-cutting themes, aimed at pedagogy students. This proposal for innovation, in pedagogical scenarios as complex and challenging as the current one, allowed the student body based on dialogue to identify critical and situated situations, expressed in three proposals of inquiry.